Epigenetic Distribution of Recombinant Plant Chromosome Fragments in a Human-Arabidopsis Hybrid Cell Line - Liaw, YengMun; Liu, Yikun; Teo, CheeHow; Cápal, Petr; Wada, Naoki; Fukui, Kiichi; Doležel, Jaroslav; Ohmido, Nobuko (International journal of molecular sciences, 2021)
Methylation systems have been conserved during the divergence of plants and animals, although they are regulated by different pathways and enzymes. However, studies on the interactions of the epigenomes among evolutionarily distant organisms are lacking. To address this, we studied the epigenetic modification and gene expression of plant chromosome fragments (~30 Mb) in a human-Arabidopsis hybrid cell line. The whole-genome bisulfite sequencing results demonstrated that recombinant Arabidopsis DNA could retain its plant CG methylation levels even without functional plant methyltransferases, indicating that plant DNA methylation states can be maintained even in a different genomic background. The differential methylation analysis showed that the Arabidopsis DNA was undermethylated in the centromeric region and repetitive elements. Several Arabidopsis genes were still expressed, whereas the expression patterns were not related to the gene function. We concluded that the plant DNA did not maintain the original plant epigenomic landscapes and was under the control of the human genome. This study showed how two diverging genomes can coexist and provided insights into epigenetic modifications and their impact on the regulation of gene expressions between plant and animal genomes.
Keywords: DNA Methylation; Epigenomics; Cell Line; epigenome; methyltransferasy; genom rostlinný; Genome, Plant; gene expression; Epigenome; Arabidopsis; metylace DNA; human–plant hybrid cell line; Repetitive Sequences, Nucleic Acid; epigeneze genetická; epigenomika; chromozomy rostlin; Chromosomes, Plant; DNA rostlinná; DNA methylation; DNA, Plant; lidé; Hybrid Cells; Humans; Arabidopsis genome; epigenom; Methyltransferases; buněčné linie; repetitivní sekvence nukleových kyselin; whole-genome bisulfite sequencing (WGBS); hybridní buňky; Epigenesis, Genetic